Quorum-quenching activity of moringa oleifera lam. (malunggay)leaves and fruit in staphylococcus aureus and pseudomonas aeruginosa. - Agbing, Jerome Abegaile E. (2015)
ABSTRACT see Upload (BIO 1400 2015)